PENDIRIAN STASIUN WILLEM I DI KOTA AMBARAWA - Sri Chiirullia Sukandar (BALAI ARKEOLOGI PAPUA, 2011)
Ambarawa in colonial times included in the residency of Semarang. Despite having a hilly landscape in the area but Ambarawa built rail networks and a station. In this city the Dutch colonial government also built a substantial fort is Fort Willem I and make Ambarawa as a military center. In addition Ambarawa area is also a growing region that the results are transported to Semarang to the colonial government and then traded to the worldwide market.